2020
DOI: 10.3390/ijms21072411
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Blood Immune Cell Populations as Biomarkers for the Outcome of Immune Checkpoint Inhibitor Therapies

Abstract: The development of cancer immunotherapy in the last decade has followed a vertiginous rhythm. Nowadays, immune checkpoint inhibitors (ICI) which include anti-CTLA4, anti-PD-1 and anti-PD-L1 antibodies are in clinical use for the treatment of numerous cancers. However, approximately only a third of the patients benefit from ICI therapies. Many efforts have been made for the identification of biomarkers allowing patient stratification into potential responders and progressors before the start of ICI therapies or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…As a result, TCR signaling during antigen presentation to naïve T cells is inhibited [13]. Therefore, in the case of persistent auto-or exo-antigenic stimulation, the PD-1/PD-L1/2 pathway plays a crucial inhibitory role [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, TCR signaling during antigen presentation to naïve T cells is inhibited [13]. Therefore, in the case of persistent auto-or exo-antigenic stimulation, the PD-1/PD-L1/2 pathway plays a crucial inhibitory role [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, the baseline percentage of circulating MDSCs inversely correlated with response to aCTLA-4 and OS. [51][52][53] Limited data exist for the effect of pembrolizumab on MDSCs. One study has shown that the baseline percentage of circulating MDSCs inversely correlated with response and OS in melanoma patients treated with nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that we did not see any differences in numbers of circulating and splenic MDSCs in any treatment group matches with recent studies [ 41 ] and may explain the final relapse of Mlh1 −/− tumors. Generally, a high frequency of memory cells and low numbers of immunosuppressive cells are indicative of a good response, though individual differences exist [ 42 ]. The Mlh1 −/− mouse model is representative for immunosuppressive subtypes, thus, converting immune regulatory cells into pro-inflammatory cell types seem challenging.…”
Section: Discussionmentioning
confidence: 99%